Injectable light-assisted thermo-responsive methylcellulose-sodium humate hydrogel proposed for photothermal ablation and localized delivery of cisplatin - Ghorbani, Farnaz; Ghalandari, Behafarid; Liu, Zichen; Li, Dejian; Yu, Baoqing (Frontiers in Bioengineering and Biotechnology, 2022)
This study aimed to develop injectable light-assisted thermo-responsive methylcellulose hydrogels filled with sodium humate, which were proposed for photothermal ablation and localized cisplatin delivery. Sodium humate converts light energy from laser beams into thermal energy, which causes methylcellulose to gel, thereby controlling the release of chemotherapy agents. Meanwhile, light emission causes to the photothermal ablation of tumor cells. For determining the optimal production conditions, different concentrations of sodium humate and light emission times were investigated. Results show that hydrogel uniformity is highly dependent on variables. An increase in sodium humate concentration and emission time resulted in a slight reduction in swelling ratio and an increase in durability. According to the simulation conditions, the cisplatin release profile was consistent with a non-Fickian mechanism with a predominant erosion contribution. In conjugation with increasing light emission time and sodium humate content, the storage modulus and viscosity increased, demonstrating hydrogel's sol-gel transition and long-lasting durability. The intrinsic fluorescence spectroscopy study revealed that the hydrogel-model protein complex empowered hydrogel bio-performance. Laser emission and cisplatin release synergistically reduced the number of viable osteosarcoma cell lines, suggesting the possibility of tumor ablation. This study describes the potential of simultaneous photothermal therapy and chemotherapy in osteosarcoma treatment, laying the groundwork for future preclinical and clinical trials.